Farmers’ Group Coaching and Agricultural Extension Regarding Soil and Water Conservation in Nagari Cupak, West Sumatra - Aditya Alqamal Alianta; Amrizal Anas; Rialdi Nurul Fahada; Mutika Putri Utama; Arini Fajriah; Dina Retno Marfu'ah; Vito Rantau (Warta Pengabdian Andalas, 2024)
Nagari Cupak is a sub-district in Solok Regency with a big rice field that can be developed to increase farmers’ wealth. The development of rice field potential in Nagari Cupak can be conducted with agricultural extension to farmers. One of the outreach topics that can deliver to farmers is the importance of the efficient functioning of farmer groups (as a learning class, as production units, and as a place to cooperate). In this situation, the topic regarding conserving water and soil in rice fields for efficient rice production in Nagari Cupak is another one that may be discussed with farmers. The agricultural extension was carried out in Jorong Panyalai, Nagari Cupak, Gunung Talang District, on Thursday, 10 August 2023. The method used in community service is the lecture method. Furthermore, it continued with a question-and-answer session. The object of this community service is to join farmer groups in Nagari Cupak, which consists of 18 farmer groups. These activities showed that the farmers did not optimise the group’s function because they only used it as a gathering place. Farmer groups also shared the issues they frequently encountered, and solutions were offered. In addition, agricultural extension activities were continued with practice regarding soil and water conservation on land provided by the Nagari Cupak Government. The farmers’ persistence can be seen in their enthusiasm for this extension activity until the end of the extension. In order to enable farmers to practice soil and water conservation on their own, they also requested that Extension Officers continue to support them.